Analisis Pemahaman dan Kesiapan Umkm Dalam Menerapkan Pencatatan Laporan Keuangan Berdasarkan Sak Emkm (Studi Kasus di Kecamatan Cimahi Utara) - Kamilah, Salma; Arafat, Fauzi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
MSMEs play an important role in the Indonesian economy, but still face obstacles in financial recording according to the EMKM SAK. This study analyzes the understanding and readiness of MSMEs in North Cimahi District in implementing these standards using a qualitative descriptive method. Data were collected through in-depth interviews with purposively selected MSMEs. The results of the study indicate that MSMEs' understanding of the EMKM SAK is still limited, with many still not implementing it in financial recording. The main inhibiting factors are the lack of socialization, minimal access to accounting education, and the assumption that financial recording does not have much impact on their business. The majority of MSMEs still use simple recording or even do not record finances at all. Therefore, further education and support from the government and related institutions are needed so that the implementation of the EMKM SAK can improve financial transparency, access to funding, and the competitiveness of MSMEs.